Peritraumatic distress and perceived mental healthcare needs among residents of a community housing during COVID-19 (Journal of Patan Academy of Health Sciences, 2020)
Introduction: The consequences of lockdown, quarantine, and uncertainties of COVID-19 pandemic has not only caused physical sufferings but affected the mental health of the people around the globe. Peritraumatic distress is a strong predictor of posttraumatic stress disorder that may further lead to depression and suicidal risk. Thus, the aim of this study was to assess peritraumatic distress and perceived mental healthcare needs among the residents of a gated community in Kathmandu Valley.Method: This was a quantitative online cross-sectional study conducted during June 2020 among adult residents of a gated community in Kathmandu Valley, Nepal. COVID-19 peritraumatic distress index and perceived mental healthcare questionnaire were used to find out peritraumatic distress and mental healthcare needs of the residents. Ethical approval was obtained. Statistical analysis of data was done using SPSS.Result: A total of 45 residents returned the completed forms. Male were 62.2%, 53.3% belonged to 36 to 55 years and 46.7% had at least one comorbidity. Mild to moderate peritraumatic distress was found among 17.82%. Fisher’s exact test showed no association between age, gender, presence of comorbidity and peritraumatic distress (p > 0.05). Perceived mental healthcare needs were felt by more than 91% of the participants.Conclusion: One sixth of the participants had mild to moderate level of peritraumatic distress. Almost all the participants felt they have mental healthcare needs. Study highlights the need for counseling for distress and mental health during COVID-19 pandemic.